A comparison of impedance models for the inverse estimation of the non-acoustical parameters of granular absorbers. (March 2016) - Cobo, Pedro; Simón, Francisco
Abstract: An impedance model relates acoustic properties of porous materials with non-acoustical parameters. Although such parameters can be measured, specific equipment is required for each of them, so that numerical methods have been proposed for estimating their value from a more manageable measurement of the normal incidence absorption coefficient in an impedance tube. This inverse procedure requires both an impedance model and an inversion technique. This paper compares four impedance models, Miki, Hamet–Berengier, Johnson–Allard–Champoux and Champoux–Stinson, when Simulated Annealing is used for the inverse estimation of the non-acoustical parameters of three granular materials, consisting of packings of small spherical glass beads of different diameters. Some of these parameters have also been measured, so that they can be compared with these estimated by the proposed inverse method.